Hubungan stigma diri dengan kualitas hidup orang dengan HIV/AIDS di Yogyakarta - Nurul Mukaromah; Ferianto Ferianto; Ratna Lestari (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Self-stigma is the acceptance of negative behavioural psychic process applied in self-concept which results in loss of self-confidence and self-efficacy. The negative label and discrimination received by PLWHA have an impact on the loss of their rights as social beings, which creates a fear of being stigmatized and hiding their health status. Objective: The aim of this research is to determine the relationship between self-stigma and the quality of life of people living with HIV/AIDS in the Gedongtengen Community Health Center Yogyakarta. Methods: This research was used the quantitative which is using the Cross-Sectional Approach. The total respondent are 77 peoples. Analysis in this study used Somers’d. Results: Obtained p value = 0,033 (p<0,05). means there are relationship between self-stigma and quality of life of PLWHA (p-value 0.033) with a weak correlation coefficient (r = -0.317). Conclusion: There is a relationship between self-stigma and the quality of life of PLWHA in the Gedongtengen Community Health Center Yogyakarta.